Spatial variability of characteristics and origins of urban wet weather pollution in combined sewers - Kafi-Benyahia, M.; Gromaire, M.G.; Chebbo, G. (4th International Conference on Sewer Processes and Networks, 2004)
An experimental on-site observatory of urban pollutant loads in combined sewers was created in the centre of Paris to quantify and characterise the dry and wet weather flow in relation to spatial scale. Eight rainfall events were studied from April 2003 to May 2004. Samples were analysed for suspended solids, organic matter, nitrogen and heavy metals. Results confirm the extent of wet weather pollution. They have shown the relative homogeneity of SS and organic matter characteristics from one urban catchment area to another. Two groups of heavy metals were identified. The first one concerns Cu, which has a higher concentration in wet weather flow (WWF) than in dry weather flow (DWF), and runoff. The second includes Cd, Pb and Zn, where higher concentrations were measured in urban runoff than in WWF and DWF. A first evaluation of contribution of wastewater, urban runoff and sewer deposit erosion sources to wet weather pollution was established and has highlighted the contribution of wastewater and sewer deposits to this pollution. However, it has shown that sewer deposit erosion remains an important source of wet weather pollution at different spatial scales.